Concentrado proteico de farelo de arroz como substituto da farinha de peixe em dietas para juvenis de jundiá (Rhamdia quelen) - Loureiro, Bruno Bianch (2016)
Our study tested the inclusion of rice meal protein concentrate (RMPC) in diets containing fish meal, to reduce their use in silver catfish (Rhamdia quelen) nutrition. Were evaluated growth parameters, body composition, deposition of nutrients, metabolic responses and digestive enzymes activities. RMPC was obtained from the Fish Farming Laboratory of the Federal University of Santa Maria, RS. During 45 days, 500 silver catfish juvenile with initial weight of 6.28 ± 0.12 g were average and randomly divided into 20 cylindrical tanks (280 L, each), connected tothermoregulated water recirculation system, two biological filters and ultraviolet filter. The fish were fed three times daily at 9: 00, 13h: 00 to 17h: 00 at apparent satiety, with diets increasing levels of inclusion of RMPC (10, 15, 20, and 30%). At end of the study, we evaluated growth parameters, body composition, nutrient deposition, digestive indices, activities of trypsin and chymotrypsin enzymes, blood parameters and liver. The data were submitted to normality test and analysis of variance and the means were compared with the Control diet by Dunnett test, except weight gain (WG) and specific growth rate (SGR), which were calculated by analysis of cubic regression. Differences were considered significant at probability level of P <0.05. There were no mortalities during the experimental period. Significant differences in body composition, feed conversion, activity of digestive enzymes and plasma parameters of the fish fed with the experimental diets were observed. Significant differences were found for lower final weight and condition factor in fish fed the RMPC10 and RMPC15 diets, as well as lower body protein deposition and daily feed intake in RMPC10 diet. WG and SGR parameters (P = 0.003 and P = 0.004) set up to the cubic regression model, indicating the optimal level of inclusion of RMPC in the diet for maximum growth (25.01% and 25.07% respectively). Fish fed the RMPC30 diet had lower protein efficiency ratio (PER) and hepatossomatic index (HSI) as well as increased activity enzyme alanine aminotransferase. Based on the results obtained, it can be seen that the inclusion of 20% RMPC in diet did not change any of the parameters analyzed in this study, showing growth performance numerically superior to the control and the other diets, demonstrating significant nutritional quality of RMPC. Therefore, adding 20% of RMPC can be used in diets for silver catfish, as an alternative protein ingredient to reduce the use of fishmeal.